Challenges in managing de novo diabetes in adults: A case report of a 47 year old male - Musialska, Dominika; Bolek, Michał; Jagieła, Bartosz; Fidyk, Monika; Kędzia, Aleksandra; Minkiewicz, Magda (Quality in Sport, 2025)
Differentiating between type 1 and type 2 diabetes in adults can be challenging, particularly in cases that do not fit the classic presentation. Misclassification occurs in a significant proportion of patients, leading to delays in appropriate treatment. This case report describes a 47-year-old male with newly diagnosed diabetes, initially treated as type 2 diabetes but exhibiting progressive hyperglycemia, weight loss, and lack of response to oral medications. Further diagnostic testing, including C-peptide measurement and autoantibody screening, was crucial in refining the diagnosis. While the absence of anti-GAD and ICA antibodies ruled out autoimmune type 1 diabetes, the patient’s clinical presentation suggested an atypical form of diabetes requiring insulin therapy. This case underscores the importance of early differential diagnosis and highlights the role of continuous glucose monitoring, C-peptide testing, and antibody screening in guiding treatment decisions. A tailored approach to diabetes classification is essential to ensure timely initiation of appropriate therapy and prevent complications.